Malaysian license plate number extraction using character segmentation / Zainab Zakaria - Zakaria, Zainab (Faculty of Computer and Mathematical Sciences, 2007)
Car License Plate Recognition (CLPR) method is a key too many traffic oriented applications such as traffic monitoring, border monitoring and in toll areas. Car License Plate Recognition (CLPR) consists of three phases: license plate detection, character segmentation and character recognition. Jabatan Pengangkutan Jalan (JPJ) has a problem to detect a non-standardized Malaysian license plate number. This project proposes to extract static image of "PUTRAJAYA" Malaysian license plate number using character segmentation. The segmentation process will divided into vertical segmentation and horizontal segmentation. This application will produce the individual character. Character segmentation is an important step in Car License Plate Recognition (CLPR). There are many dif-faculties in this step, such as the influence of image noise, plate frame, rivet, the space mark and so on.